Does L2 influence on use of L1 animacy constraints depend on alignment of syntactic and semantic features?: Evidence from Japanese–English bilinguals - Lebkuecher, Amy; Malt, Barbara C. (The international journal of bilingualism : cross-disciplinary, cross-linguistic studies of language behavior, 2024)
Aims and Objectives: English allows inanimate objects to be sentence subjects (e.g., “The knife cut the bread”) but Korean and Japanese restrict subjects of causal sentences on the basis of animacy. In previous work, we found that Korean speakers relaxed their native grammatical animacy constraint when immersed in English (e.g., found knives to be acceptable sentence subjects in Korean). We suggested this L2 influence occurred because the Korean animacy constraint does not map cleanly onto the semantic representation of animacy—some inanimate objects (e.g., “fire”) can be subjects of causal sentences. In the current study, we further test this idea by examining the case of Japanese–English bilinguals. We predict that because the Japanese animacy constraint aligns well with the semantic representation of animacy, it will be less susceptible to L2 influence. Methodology: We first independently assessed the semantic representation of animacy by comparing animacy ratings from native speakers of Korean, Japanese, and English for 60 objects. We then asked Japanese–English bilinguals and Japanese monolinguals to provide grammaticality judgments for sentences that varied in subject animacy. Data and Analysis: We analyzed participants’ animacy ratings and grammaticality judgments using mixed-effects models. Findings: Animacy ratings supported a closer correspondence between semantic representation of animacy and the grammatical animacy constraint for Japanese grammar than for Korean grammar. In contrast to previous results for Korean speakers, Japanese–English bilinguals’ grammaticality judgments did not significantly differ from those of Japanese monolinguals. Originality: The current study is unique in that it suggests the vulnerability of structures at the syntax–semantics interface to L2 influence varies across different language groups based on the alignment between syntactic and semantic features. Implications: The current findings support the possibility that representations at the syntax–semantics interface may only be vulnerable to influence when syntax is incongruent with semantic features.